Clover: The CMB polarization observer - Maffei, B; Ade, P; Calderon, C; Challinor, A; De Bernardis, P; Dunlop, L; Gear, W; Giraud-Heraud, Y; Goldie, D; Grainge, K; Isaak, K; Johnson, B; et al. (2005)
We present a new, fully-funded ground-based instrument designed to measure the B-mode polarization of the Cosmic Microwave Background (CMB). The concept is based on three independent subsystems operating at 90, 150 and 220 GHz, each comprising a telescope and a focal plane of horn-coupled background-limited bolometers. This highly-sensitive experiment, planned to be based at Dome C station in Antarctica, is optimised to produce very low systematic effects. It will allow the detection of the CMB polarization over angular multipoles 20 < l < 1000 accurately enough to measure the B-mode signature from gravitational waves to a lensing-confusion-limited tensor-to-scalar ratio r similar to 0.005.